2015
DOI: 10.1097/brs.0000000000000914
|View full text |Cite
|
Sign up to set email alerts
|

Part 3

Abstract: 5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…Following the results of a pilot study considering the dimensions of the scanner (Siemens Magnetom Aera 1.5T, Erlangen, Germany), it was calculated that subjects taller than 183cm were needed to allow performance of the SLR in the scanner, permitting at least 60° of unrestricted hip flexion [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the results of a pilot study considering the dimensions of the scanner (Siemens Magnetom Aera 1.5T, Erlangen, Germany), it was calculated that subjects taller than 183cm were needed to allow performance of the SLR in the scanner, permitting at least 60° of unrestricted hip flexion [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Rade and colleagues demonstrated conus medullaris caudal displacement of 2.33± 1.2 mm with the unilateral SLR and 4.58±1.48 mm with the bilateral SLR, both tests to 50° hip flexion [ 1 , 18 ]. Moreover, at 60° SLR the conus caudal displacement was shown to increase, with 3.54 ± 0.87 mm of caudal displacement with unilateral SLR and 7.42 ± 2.09 mm with bilateral SLR [ 19 ]. In both studies it emerged that the magnitude of conus medullaris displacement with unilateral SLR was doubled with the bilateral SLR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the sliding or craniocaudal movement of the neural structures within the vertebral canal should be considered a protective mechanism, which represents transmission of tensile forces through the neural structures, thereby preserving the spinal cord and nerve roots from excessive strain ( 14 ). Therefore, maintaining free sliding of the neural structures and meninges has been considered an essential condition for maintaining a healthy and normal functioning spinal cord ( 13 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…The variation of conus medullaris termination between and possibly within breeds makes it difficult to objectively quantify the normal degree of conus medullaris displacement in unaffected dogs. In humans, the degree of hip flexion has also been associated with differences in magnitude of conus medullaris displacement, and therefore, variations can be seen between and within individual patients ( 13 ). Although a diagnosis of tethered cord syndrome with a tight filum terminale was suspected based on the subjective observation of decreased to absent conus medullaris displacement between extended and flexed positions, further studies are necessary to evaluate if this finding can be used as a reliable diagnostic criterion for this rare congenital disorder.…”
Section: Discussionmentioning
confidence: 99%